Combination Treatment with Cryolipolysis and Hyaluronic Acid Fillers for Jawline Enhancement - Shimojima K; Hashimoto M; Yamaoka Y; Kapoor KM (Clinical, Cosmetic and Investigational Dermatology)
Kumiko Shimojima,1 Mayuko Hashimoto,1 Yuhi Yamaoka,1 Krishan Mohan Kapoor2 1Kumiko Clinic, Tokyo, Japan; 2Anticlock Clinic, Chandigarh, IndiaCorrespondence: Krishan Mohan Kapoor, Department of Plastic Surgery, Anticlock Clinic, #1508, Sector 33-D, Chandigarh, 160022, India, Tel +91-9876600600, Email kmkapoor@gmail.comBackground: Facial contouring procedures are increasingly sought to address aesthetic concerns such as submental fat accumulation and lack of jawline definition. Cryolipolysis and hyaluronic acid (HA) injection have emerged as promising modalities for lower face contouring, targeting fat reduction and jawline enhancement, respectively.Objective: This study aims to assess the efficacy and safety of a combined treatment approach involving cryolipolysis followed by HA injection for addressing lower face contour concerns. Specifically, the study seeks to evaluate outcomes associated with this comprehensive treatment modality in the lower face region.Methods: A retrospective analysis was conducted on four females and one male who underwent cryolipolysis treatment for double chin reduction, followed by HA injection for jawline contouring. Pre- and post-treatment assessments, including digital photographs and standardized measurements, were performed to evaluate changes in lower face contouring. Objective evaluation of treatment outcomes was facilitated using digital photographs and standardized measurements, including 3-D images captured using the VECTRA system. Post-treatment assessments were conducted at 4-week intervals to monitor progress, with participant satisfaction assessed using the Global Aesthetic Improvement Scale (GAIS) at the end of six months after filler treatment.Results: Findings from this pilot study demonstrate significant improvement in lower face contouring resulting from the combined treatment of cryolipolysis and HA injection. Post-treatment improvements included reduced submental fullness, enhanced definition in the jawline and improved chin projection. The cervicomental angle, measured using VECTRA, demonstrated a reduction post-treatment in all subjects. After Cryolipolysis only, the mean change in cervicomental angle was − 4.94°, with a p-value of 0.0635. After both cryolipolysis and fillers, the mean change in cervicomental angle was − 9.34°, and the p-value was 0.0244, indicating a statistically significant reduction. Subjective reports from participants, using GAIS, indicated high satisfaction with treatment outcomes.Conclusion: These results indicate that while cryolipolysis alone shows a trend toward improvement, the addition of hyaluronic acid fillers provides a statistically significant enhancement in cervicomental angle and overall lower face contouring. Hence, integrating cryolipolysis and HA injections offers a comprehensive solution for addressing lower face contour concerns, providing synergistic benefits for both modalities.Keywords: fillers, cryolipolysis, jawline fillers, chin fillers, hyaluronic acid